2018
DOI: 10.3390/nu10111568
|View full text |Cite
|
Sign up to set email alerts
|

Association between Gestational Weight Gain, Gestational Diabetes Risk, and Obstetric Outcomes: A Randomized Controlled Trial Post Hoc Analysis

Abstract: Excess gestational weight gain (GWG) is associated with the development of gestational diabetes mellitus (GDM). Lifestyle trials have not achieved much GWG limitation, and have largely failed to prevent GDM. We compared the effect of substantial GWG limitation on maternal GDM risk. Pregnant women with a body mass index (BMI) ≥29 kg/m2 <20 weeks gestation without GDM (n = 436) were randomized, in a multicenter trial, to usual care (UC), healthy eating (HE), physical activity (PA), or HE and PA lifestyle interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 29 publications
(44 reference statements)
2
14
0
Order By: Relevance
“…Interestingly, a post hoc analysis of data from DALI (Vitamin D and Lifestyle Intervention for GDM Prevention) study failed to confirm any correlation between smaller gestational weight gain and improvement in maternal glycemia, whereas a long--term follow-up of over 900 mother-child pairs recruited at one site within the HAPO study found that both excessive and insufficient gestational weight gain was associated with an increased risk of insulin resistance and hypertensive disorders in children at the age of 7 years. 49,50 It should be also noted that IOM recommendations for gestational weight gain were set for a general population of pregnant women and are related to maternal BMI only. 51 Hence, there is still a controversy whether only weight gain IOM recommendations are also relevant in pregnancies complicated with maternal diabetes or prediabetes, and whether any adjustments in GWG with more attention to maternal lipids would contribute to a reduction of increased fetomaternal risk, specific for this population of pregnant women.…”
Section: Knowledge Gaps and Area For Future Researchmentioning
confidence: 99%
“…Interestingly, a post hoc analysis of data from DALI (Vitamin D and Lifestyle Intervention for GDM Prevention) study failed to confirm any correlation between smaller gestational weight gain and improvement in maternal glycemia, whereas a long--term follow-up of over 900 mother-child pairs recruited at one site within the HAPO study found that both excessive and insufficient gestational weight gain was associated with an increased risk of insulin resistance and hypertensive disorders in children at the age of 7 years. 49,50 It should be also noted that IOM recommendations for gestational weight gain were set for a general population of pregnant women and are related to maternal BMI only. 51 Hence, there is still a controversy whether only weight gain IOM recommendations are also relevant in pregnancies complicated with maternal diabetes or prediabetes, and whether any adjustments in GWG with more attention to maternal lipids would contribute to a reduction of increased fetomaternal risk, specific for this population of pregnant women.…”
Section: Knowledge Gaps and Area For Future Researchmentioning
confidence: 99%
“…This may be, in part, due to neurohormonal gut-brain interactions in women with PCOS [ 6 ]. GWG in women is crucial to optimize maternal, fetal, and neonatal health, with previous studies associating inappropriate pre-pregnancy BMI and GWG with higher risks of adverse neonatal and maternal outcomes in general pregnant women [ 7 10 ]. However, few studies have described the impact of both pre-pregnancy BMI and GWG on maternal and infant outcomes of these special individuals.…”
Section: Introductionmentioning
confidence: 99%
“…For example, women with PCOS are more prone to be overweight/obese and to experience higher GWG, than their normal counterparts (4,5). GWG in women is crucial to optimize maternal, fetal, and neonatal health, with previous studies associating inappropriate pre-pregnancy BMI and GWG were at higher risks of adverse neonatal and maternal outcomes in general pregnant women (6)(7)(8)(9)(10)(11). However, few studies have described the impact of both pre-pregnancy BMI and GWG on maternal and infant outcomes of this special individuals.…”
Section: Introductionmentioning
confidence: 99%